Censorship detected in TR (Turkey) - Voidly (Voidly Global Censorship Index, 2025)
WARNING severity censorship detected in Turkey. Data sourced from CensoredPlanet.
Censorship Incident ID: TR-2025-0004. Severity: warning. Confidence: 75%